Dynamic Changes in the Antioxidative Defense System in the Tea Plant Reveal the Photoprotection-Mediated Temporal Accumulation of Flavonoids under Full Sunlight Exposure. (31st August 2022) - Zhang, Qunfeng; Ruan, Jianyun; Mumm, Roland; de Vos, Ric C H; Liu, Mei-Ya
Abstract: To reveal the mechanisms underlying how light affects flavonoid metabolism and the potential role of flavonoids in protecting against photooxidative stress in tea leaves, tea plants adapted to low-light conditions were exposed to full sunlight over 48 h. There was an increase in the activities of catalase (CAT) and superoxide dismutase (SOD) as well as greater accumulation of reactive oxygen species, lutein, tocopherols, ascorbate and malondialdehyde, suggestive of a time-dependent response to photooxidative stress in tea leaves. Analysis of the time dependency of each element of the antioxidant system indicated that carotenoids and tocopherols exhibited the fastest response to light stress (within 3 h), followed by SOD, CAT and catechin, which peaked at 24 h. Meanwhile, flavonols, vitamin C and glutathione showed the slowest response. Subsequent identification of the main phytochemicals involved in protecting against oxidative stress using untargeted metabolomics revealed a fast and initial accumulation of nonesterified catechins that preceded the increase in flavonol glycosides and catechin esters. Gene expression analysis suggested that the light-induced accumulation of flavonoids was highly associated with the gene encoding flavonol synthase. Ultraviolet B (UV-B) irradiation further validated the time-dependent and collaborative effects of flavonoids in photoprotection in tea plants. Intriguingly, the dynamics of the metabolic response are highly distinct from those reported for Arabidopsis, suggesting that the response to light stress is not conserved across plants. This study additionally provides new insights into the functional role of flavonoids in preventing photooxidative stress and may contribute to further improving tea quality through the control of light intensity.